EKSISTENSI LEMBAGA EKONOMI SYARIAH DALAM PEMBANGUNAN EKONOMI UMAT - Djaenab Djaenab (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2021)
Sharia economics is an economy based on divine revelations that were revealed for the benefit and welfare of mankind. Its presence as a solution based economic system is a tangible manifestation that sharia values can be implemented in all aspects of life, including the economiy. This is evidenced by the development of islamic economic institutions, both bank and non-banks. Sharia economy as an economic system that frees itself from the practice of ribā, maesyir, and gharar transactions which is one of the causes of the destruction of the globaleconomic order, comes with instruments that can provide solutions for the creation of economic development of the people that will have an impact on the welfare of society, both materially and spiritually. For example; ribā transactions are replaced with “profit and loss sharing” instruments with the principles of mudhārabah (trustee profit sharing) dan musyārakah (joint venture profit sharing), maesyir transaction are replaced with anta rādin minkum instruments (the willingness of the transacting parties), gharar transaction are repalced with open transactions. Furthermore, in its operational framework, the instrument is integrated into the five pillars of the islamic economic fundation, namely; Tauhīd, ‘Adl, Nubuwwah, Khilāfah, Ma’ad.